Dayah Diniyah Darussalam: Protecting and economic empowering women and children’s victims of violence - Mellyan, Mellyan; Junaidi, Junaidi (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2026)
Dayah Diniyah, led by Ummi Hanisah, is concerned with the issue of protecting women and children’s victims of violence. The purpose of this study is to determine how Dayah Diniyah Darussalam maintains its existence as a center for protection, economic empowerment, and handling of women and children’s victims of violence and to know the challenges and obstacles faced by Dayah Diniyah Darussalam, West Aceh in providing protection, treatment, and economic empowerment to women and children victims of violence. This study uses a qualitative method with a descriptive analysis approach. Data collection was carried out using observation, interviews, and documentation. The results of the study show; In addition to religious knowledge, Dayah Diniyah Darussalam also teaches economic independence through gardening, catfish and bee farming, bamboo crafts and screen printing so that survivors become independent and self-sufficient. The challenges faced include, firstly, the negative stigma against Dayah, which is considered a place to accommodate people with problems. Secondly, bullying is still experienced against economic empowerment activities carried out because it is considered a dayah for growing vegetables, not a dayah for reciting the Koran. Thirdly, there is not yet maximum support from the government regarding ecological-based economic empowerment activities. Fourthly, the desire to introduce an Ecological Curriculum or Environmental Fiqh in the Dayah curriculum has not been realized. Fifthly, there is no permanent psychologist available to handle the victims. Sixthly, there is no fixed budget, as most of the funding comes from donations and charity given by generous people.